Applications of Chiral Three-membered Rings for Total Synthesis: A Review - Dalpozzo, Renato; Lattanzi, Alessandra; Pellissier, Helene (Current Organic Chemistry, 2017)
This review updates recent applications of asymmetric aziridination, azirination, thiirination, epoxidation, and cyclopropanation in the total synthesis of biologically active compounds, including natural products, using chiral substrates or chiral catalysts, covering the literature since 2000. The interest towards these synthetic methodologies of chiral three-membered rings has increased in the last decade, dictated either by the biological activities that display many naturally occurring products bearing a three-membered unit or by the ring strain of three-membered rings making them useful precursors of many more complex interesting molecules. Classic as well as modern protocols in asymmetric aziridinations, azirinations, epoxidations, thiirinations, and cyclopropanations have been widely applied as key steps of a number of syntheses of important products. Although the use of chiral substrates and auxiliaries is still highly employed particularly in asymmetric aziridination and cyclopropanation, the development of enantioselective catalytic methodologies has witnessed exponential growth during the last decade. The present review is subdivided into three parts, dealing successively with the use of chiral nitrogen-containing three-membered rings, chiral epoxides and thiiranes, and chiral cyclopropanes in total synthesis.
Keywords: natural products